Lipid Vesicle Detection using ISFET devices - Juan Carlos Briceño; Juan Carlos Ortiz Pereira; Alba Graciela Ávila; Ivan Adolfo Rey; Chad Leidy (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
The Ion Sensitive Field Effect (ISFET) Transistors are electronic devices widely used for detecting, ion concentrations, trapped charge or charge decay processes. This article reports on the electrical characterization of ISFETs exposed to buffer solutions sets at pH 4, 5, 7, and 10. When operated in their saturation regime ISFETs act as local charge detectors. This capability is applied to detect lipid vesicles. Lipid vesicles have promising applications in drug delivery, and their accurate detection can be important in understanding their interaction with living systems.